Law & ethics for medical careers - Judson, Karen (McGraw-Hill Higher Education, 2010)
Offers an overview of the laws and ethics that readers should know to help give competent, compassionate care to patients that is within acceptable legal and ethical boundaries. This book features pertinent legal cases, anecdotes, and sidebars related to health-related careers